Book Review of Frisbie's A Therapist’s Guide to Treating Eating Disorders in a Social Media Age. - Sharpe, Hillary (Canadian Journal of Counselling and Psychotherapy, 2021)
Eating disorders and other “sub-clinical” problems such as disordered eating and body shame/dissatisfaction grow more prevalent in our society. This is particularly true since the advent of COVID-19 changed our social landscape, leading to increases in isolation and anxiety and in the use of technology to work, to connect, and to live. Social media in this age present both barriers and possibilities for mental health and identity development, particularly for individuals who suffer from eating disorders and related problems. In her seminal first book, Shauna Frisbie deftly weaves through each of these topics, creating a tapestry for both novice and expert clinicians to view and understand how social media consumption can be assessed, dismantled, and harnessed to help clients who struggle with disordered eating. Guided by the central topics of selfhood and identity development and by the techniques of phototherapy, Dr. Frisbie creates a compelling story that draws on both research and case studies from her practice.